Maqasid Syariah in Islamic Consumption - Ahmad Musadik, Siti Hajar Salwa; Yusuff, Noraini; Abd Aziz, Noriza; Abdul Ghani Azmi, Ilhaamie (Academia Industry Networks, 2020)
Emerging issues in consumption among Muslim consumers are constantly changing from small scale towards immense issues such as overspending, massive debt, bankruptcy, and financial crime which resulted into detrimental effect on life and society. Islam never prohibited consumerism, but Islamic doctrine stipulated the rule and regulation in consumption. There are things compulsory to practice and to avoid in consumption activities. Practicing activity that leads to negative consequences such as spending wealth inappropriately is definitely disapproved in Islamic doctrine. Therefore, the objective of this conceptual paper is to review the concept of Islamic consumption from Maqasid Syariah perspective which consists of three major classifications of maqasid shariah namely; daruriyyah (necessities), hajiyah (needs), and tahsiniyyah (luxuries), and the five fundamentals of necessities namely; preserving of religion (al-Din), preserving of life (al-Haya), preserving of wealth (al-Mal), preserving of mind (al-Aql), and preserving of lineage (nasab). A sound comprehension of Islamic consumption from Maqasid Syariah's perspective will efficiently lead to wise consumption